Emerging organic contaminants in the River Ganga and key tributaries in the middle Gangetic Plain, India: Characterization, distribution & controls. (15th June 2023) - Richards, Laura A.; Guo, Shuaizhi; Lapworth, Dan J.; White, Debbie; Civil, Wayne; Wilson, George J.L.; Lu, Chuanhe; Kumar, Arun; Ghosh, Ashok; Khamis, Kieran; Krause, Stefan; Polya, David A.; et al.
Abstract: The presence and distribution of emerging organic contaminants (EOCs) in freshwater environments is a key issue in India and globally, particularly due to ecotoxicological and potential antimicrobial resistance concerns. Here we have investigated the composition and spatial distribution of EOCs in surface water along a ∼500 km segment of the iconic River Ganges (Ganga) and key tributaries in the middle Gangetic Plain of Northern India. Using a broad screening approach, in 11 surface water samples, we identified 51 EOCs, comprising of pharmaceuticals, agrochemicals, lifestyle and industrial chemicals. Whilst the majority of EOCs detected were a mixture of pharmaceuticals and agrochemicals, lifestyle chemicals (and particularly sucralose) occurred at the highest concentrations. Ten of the EOCs detected are priority compounds ( e.g. sulfamethoxazole, diuron, atrazine, chlorpyrifos, perfluorooctane sulfonate (PFOS), perfluorobutane sulfonate, thiamethoxam, imidacloprid, clothianidin and diclofenac). In almost 50% of water samples, sulfamethoxazole concentrations exceeded predicted no-effect concentrations (PNECs) for ecological toxicity. A significant downstream reduction in EOCs was observed along the River Ganga between Varanasi (Uttar Pradesh) and Begusarai (Bihar), likely reflecting dilution effects associated with three major tributaries, all with considerably lower EOC concentrations than the main Ganga channel. Sorption and/or redox controls were observed for some compounds ( e.g. clopidol), as well as a relatively high degree of mixing of EOCs within the river. We discuss the environmental relevance of the persistence of several parent compounds (notably atrazine, carbamazepine, metribuzin and fipronil) and associated transformation products. Associations between EOCs and other hydrochemical parameters including excitation emission matrix (EEM) fluorescence indicated positive, significant, and compound-specific correlations between EOCs and tryptophan-, fulvic- and humic-like fluorescence. This study expands the baseline characterization of EOCs in Indian surface water and contributes to an improved understanding of the potential sources and controls on EOC distribution in the River Ganga and other large river systems. Graphical abstract: Image 1 Highlights: Emerging organic contaminants (EOCs) widely detected in River Ganga and tributaries. Pharmaceuticals and agrochemicals were the dominant type of EOCs. Lifestyle compounds such as sweeteners dominated EOC concentrations. Dilution impacts from tributaries with lower EOC concentrations was a major control. EOCs were associated with other hydrochemical, including fluorescence, properties.